The Pralogical Essence of the Implicit Order - Yatsenko, Tamara S. (Psychological Counseling and Psychotherapy, 2020)
The article presents the research results of the archaic genesis of the implicit order. This term has been implemented into scientific use for more than a decade, however, it has so far been little described and lacked scientific substantiation. The article draws our attention to the fact that the implicit order of the psyche unites diametrically opposed tendencies that primarily correspond to the basic conflict “life ↔ death”. The sequence (order) of psychoanalytical analysis of art reproductions (selected for self-presentation) is set by a respondent, which proves the existence of blind hand skill. The implicit order proves the power of the basic law of pralogical thinking - involvement - which governs the pralogical thinking integrated with a modern person’s reflexive, social and perceptive thinking. The article presents the results based on the stenographic material analysis of deep cognition of the psyche: audio and video of ASPC processes using thematic psycho-drawings “Fault tattoo” and “Own tattoo”. The main argument of the pralogical essence of the implicit order is based on its main characteristic – neutrality to the discrepancy of its components which is exactly its pralogical essence. The ASPC participants arrange the visualized self-presenters ignoring (not noticing) their contradiction (conflict). The research gives an opportunity to state the connection of the “order” with the basic psyche conflict: “life” ↔ “death”. The diagnostic-corrective process ASPC can actualize the self-preservation instinct by expanding the borders of subject’s self-awareness with the increase of the behavior rationality, i.e. logical thinking efficiency.